Antarctica as a reservoir of planetary analogue environments - Cassaro A.; Pacelli C.; Aureli L.; Catanzaro I.; Leo P.; Onofri S. (Extremophiles, 2021)
One of the main objectives of astrobiological research is the investigation of the habitability of other planetary bodies. Since space exploration missions are expensive and require long-term organization, the preliminary study of terrestrial environments is an essential step to prepare and support exploration missions. The Earth hosts a multitude of extreme environments whose characteristics resemble celestial bodies in our Solar System. In these environments, the physico-chemical properties partly match extraterrestrial environments and could clarify limits and adaptation mechanisms of life, the mineralogical or geochemical context, and support and interpret data sent back from planetary bodies. One of the best terrestrial analogues is Antarctica, whose conditions lie on the edge of habitability. It is characterized by a cold and dry climate (Onofri et al., Nova Hedwigia 68:175–182, 1999), low water availability, strong katabatic winds, salt concentration, desiccation, and high radiation. Thanks to the harsh conditions like those in other celestial bodies, Antarctica offers good terrestrial analogues for celestial body (Mars or icy moons; Léveillé, CR Palevol 8:637–648, https://doi.org/10.1016/j.crpv.2009.03.005, 2009). The continent could be distinguished into several habitats, each with characteristics similar to those existing on other bodies. Here, we reported a description of each simulated parameter within the habitats, in relation to each of the simulated extraterrestrial environments.